Electron transporter for electron transport layer of perovskite solar cell, coating agent for electron transport layer comprising same, electron transport layer, and perovskite solar cell

By using metal oxide nanoparticles modified with phosphorus salt surface, the electron transfer layer of perovskite solar cells is prepared, and the problems of complex processes and high-temperature treatment in the prior art are solved, and efficient and uniform electron transfer layer formation is achieved, which improves the performance of solar cells.

CN119896070APending Publication Date: 2025-04-25HANWHA SOLUTIONS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380064161.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-20
Filing Date
2023-09-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When preparing the electron transfer layer, the existing perovskite solar cells have complex processes and are prone to damage the light absorption layer with high temperature treatment. The formation method of the organic binder coating layer has decomposition problems, which affects flexibility and performance.

Method used

The electron transfer layer is prepared by applying metal oxide nanoparticles modified from the surface of the phosphorus salt as the electron transfer body, and the electron transfer layer is prepared by a dispersion type coating agent to avoid high temperature treatment and form an ultra-thin film to protect the light absorption layer.

Benefits of technology

The electron transfer layer is formed at a low temperature heat treatment below 200°C, which avoids damage to the light absorption layer, improves the uniformity of the film and the performance of the solar cell, including open voltage, fill factor and photoelectric conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896070A_ABST
    Figure CN119896070A_ABST
Patent Text Reader

Abstract

The present invention relates to a coating agent for forming an electron transfer layer (or an electron transport layer), and relates to a reverse-structure perovskite using surface-modified metal oxide nanoparticles provided as a coating agent prepared in a dispersion type to form an electron transfer layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electron transfer layer (ETL) for perovskite solar cells

[0002] on transport layer) forming coating agent, electron carrier used therefor, and the coating agent

[0003] An electron transport layer formed by an agent and a perovskite solar cell comprising the same.

[0004] This application claims the rights of Korean Patent Application No. 10-2022-2022-

[0005] The entire contents of the priority and benefits of No. 0118424 are included in this specification. Background Art

[0006] In order to solve the depletion of fossil energy and the global environmental problems caused by its use, solar energy,

[0007] Active research is underway into renewable, clean alternative energy sources such as wind power and water power.

[0008] Among them, interest in solar cells that directly convert sunlight into electrical energy has greatly increased.

[0009] Among them, solar cells refer to the use of light energy absorbed from sunlight to generate electrons and holes.

[0010] A battery that generates current and voltage through the voltaic effect.

[0011] Currently, np diode-type silicon (S) with a light energy conversion efficiency greater than 20% can be prepared.

[0012] i) Single crystal solar cells are used in actual solar power generation and have a higher conversion efficiency.

[0013] However, in order to achieve high efficiency, solar cells based on inorganic semiconductors need to be made of extremely high purity.

[0014] Purified raw materials, thus purifying raw materials consumes a lot of energy, and in the use of raw materials

[0015] The process of single crystal or thin film production requires expensive process equipment, which reduces the efficiency of solar cells.

[0016] The cost of preparing the pool is limiting, and has become a stumbling block to large-scale utilization.

[0017] Therefore, in order to prepare solar cells at a low cost, it is necessary to greatly reduce the amount of

[0018] The cost of the core raw materials or manufacturing process of the battery is

[0019] As an alternative to energy-saving batteries, research is underway into perovskites that can be prepared using low-cost raw materials and processes.

[0020] Solar cell.

[0021] Recently, a perovskite solar cell using (NH3CH3)PbX3 (X = I, Br, Cl) as a photoactive body has been developed and research is underway for commercialization. The general structural formula of the perovskite structure is an ABX3 structure, with anions at the X position, larger cations at the A position, and smaller cations at the B position.

[0022] Perovskite solar cells, which are organic metal halogen compounds with the molecular formula (CH3NH3)PbX3, were first used as photoactive bodies in solar cells in 2009. Since then, since the development of solid-state perovskite solar cells with the current structure in 2012, the efficiency has increased rapidly. Conventional perovskite solar cells use metal oxides as electron transfer layers, and mainly use organic substances or polymers such as spiro-OMETAD as hole transport layers (HTL). That is, a metal oxide porous film or thin film is made on a transparent electrode such as FTO, a perovskite material is applied, then a hole transport layer is applied, and then an electrode layer such as gold (Au) or silver (Ag) is deposited.

[0023] The important issues for the commercialization of perovskite solar cells are to ensure stability and flexible technology. The existing electron transfer layer formed by metal oxide on the photoactive layer is formed by depositing metal oxide or coating metal oxide on the photoactive layer (or light absorbing layer), and then forming a separate organic binder coating layer thereon. However, when the metal oxide is deposited to form, the preparation process is complicated and varied, which greatly increases the preparation cost, and there is a disadvantage that the physical and chemical energy generated during the deposition process may damage the light absorbing layer. In addition, in the method of forming the organic binder coating layer, a high-temperature heat treatment is performed to form the coating layer, and the perovskite has the problem of decomposition at a high temperature of more than 200°C, which reduces the flexibility of the solar cell and reduces the application range of the perovskite solar cell. When a dispersant is used to form a uniform thin film of the electron transfer layer, a high-temperature (more than 500°C) heat treatment process is required to remove the dispersant, so it also has the problem of causing damage to the perovskite layer.

[0024] Furthermore, when a passivation layer made of a fullerene-based raw material is formed between the perovskite light-absorbing layer and the electron-transporting layer, damage to the light-absorbing layer can be prevented to a certain extent. However, depending on the raw material of the electron-transporting layer, there is a problem that the electron-transporting body reacts with the fullerene in the passivation layer, damaging the passivation layer and causing a decrease in the performance of the solar cell element. Summary of the invention

[0025] Technical issues

[0026] In order to overcome the above-mentioned problems, the present invention has conceived that metal oxide nanoparticles whose surfaces are modified from specific raw materials are used as electron transfer bodies for electron transfer layers (or electron transport layers, ETL (Electron Transporting Layer)) and coating agents for forming electron transfer layers using the electron transfer bodies, and coating agents and electron transfer layers prepared therefrom in a dispersion type are formed to provide perovskite solar cells with excellent performance.

[0027] Solutions to the problem

[0028] In order to solve the above problems, the present invention is an invention of an electron transporter for an electron transport layer (ETL) of a perovskite solar cell, comprising metal oxide nanoparticles surface-modified with a phosphorus salt represented by the following Chemical Formula 1.

[0029] Chemical formula 1

[0030]

[0031] In Chemical Formula 1, R 1 To R 4 C1~C 10 Straight chain alkyl, C3~C 10 The above X is a halogen atom or -OH.

[0032] As a preferred embodiment of the present invention, the above-mentioned metal oxide nanoparticles may include oxides containing one or more metals selected from tin (Sn), zirconium (Zr), strontium (Sr), zinc (Zn), vanadium (V), molybdenum (Mo), tungsten (W), niobium (Nb), aluminum (Al) and gallium (Ga).

[0033] As a preferred embodiment of the present invention, the above-mentioned metal oxide nanoparticles may include one or more selected from SnO2, ZnO, TiO2, CeO2, ZrO2, WO3, Zn2SnO4, BaSnO3 and SrTiO3.

[0034] As a preferred embodiment of the present invention, the particle size of the metal oxide nanoparticles may be 2-100 nm.

[0035] As a preferred embodiment of the present invention, the electron carrier of the present invention may include 85.0-95.0 wt % of the above metal oxide nanoparticles and the remaining amount of the surface modification component in the total weight.

[0036] Another object of the present invention is to provide a coating agent for an electron transport layer of a perovskite solar cell, which is a dispersion in which the electron transporter described above is dispersed, and comprises an organic solvent and the electron transporter dispersed in the organic solvent.

[0037] As a preferred embodiment of the present invention, the coating agent for an electron transport layer of a solar cell of the present invention may include 0.30 to 2.00 wt % of an electron transporter and the remainder of an organic solvent.

[0038] As a preferred embodiment of the present invention, the dielectric constant of the organic solvent may be less than 20.

[0039] As a preferred embodiment of the present invention, the organic solvent may include at least one selected from isopropanol, butanol, 2,2,2-trifluoroethanol, chlorobenzene and ethyl acetate.

[0040] Furthermore, another object of the present invention is to provide an electron transport layer of a perovskite solar cell including a coating layer formed of the coating agent described above.

[0041] As a preferred embodiment of the present invention, the thickness of the electron transport layer may be 10-100 nm.

[0042] As a preferred embodiment of the present invention, when the thickness of the electron transport layer is 10 to 15 nm, the transmittance of light with a wavelength of 500 to 550 nm can be 88.0% or more.

[0043] Furthermore, another object of the present invention is to relate to a perovskite solar cell including the above-mentioned electron transfer layer, wherein the electron transfer layer described in claim 8 can be directly formed on the upper surface of the perovskite light absorbing layer, or a passivation layer is formed between the perovskite light absorbing layer and the electron transfer layer described in claim 8.

[0044] Effects of the Invention

[0045] The coating agent for forming the electron transfer layer of the present invention can form an ultra-thin film by low-temperature heat treatment below 200°C without requiring a high-temperature treatment process for forming a thin film, thereby preventing damage to the perovskite light absorption layer, and does not chemically react with the surface modification component of the electron transfer body in the coating agent and the fullerene raw material of the passivation layer, thereby preventing damage to the passivation layer. In addition, the electron transfer layer formed by the coating liquid of the present invention can be provided with high film uniformity, and the open voltage (V OC , open-circuit voltage) and fill factor (FF, fill factor) are excellent, due to high light transmittance, short-circuit current (J sc , short-circuit current) and a solar cell with outstanding photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is the TEM measurement image of the SnO2 nanoparticles prepared in Example 1.

[0047] Figure 2 This is the XRD measurement curve of the SnO2 nanoparticles prepared in Example 1.

[0048] Figure 3 FT-IR measurement curves of the unmodified SnO2 nanoparticles (control SnO2) and the surface-modified SnO2 nanoparticles prepared in Example 1.

[0049] Figure 4 It is a TGA measurement curve diagram of the unmodified SnO2 nanoparticles (control SnO2) and the surface-modified SnO2 nanoparticles prepared in Example 1.

[0050] Figure 4 (a) is a photograph of a solution in which unmodified SnO2 nanoparticles are dispersed in isopropyl alcohol, and (b) is a photograph of the coating solution for forming an electron transport layer prepared in Example 1.

[0051] Figure 5 These are dynamic light scattering particle size analysis measurement curves of Example 2-1 (TBPH), Comparative Example 2-2 (TBAH), and Comparative Example 2-3 (TMAH) implemented in Experimental Example 2.

[0052] Figure 6 These are the measurement results of the current density of the inverse structure perovskite solar cells prepared in Preparation Example 1 (TPBH), Comparative Preparation Example 2 (TBAH), and Comparative Preparation Example 3 (TMAH) implemented in Experimental Example 2.

[0053] Figure 7 These are the results of measuring the current density of the silicon / perovskite tandem solar cells prepared in Preparation Example 4 (TPBH), Comparative Preparation Example 2 (TBAH), and Comparative Preparation Example 3 (TMAH) implemented in Experimental Example 3. DETAILED DESCRIPTION

[0054] Hereinafter, the present invention will be described in more detail.

[0055] The present invention relates to an electron transporter suitable for an electron transport layer (or electron transport layer, ETL) of an inverse structure perovskite solar cell and a dispersion type coating agent using the electron transporter.

[0056] The electron mediator of the present invention includes metal oxide nanoparticles surface-modified with a phosphorus salt represented by the following Chemical Formula 1.

[0057] Chemical formula 1

[0058]

[0059] In Chemical Formula 1, R 1 To R 4 C1~C 10 Straight chain alkyl, C3~C 10 branched alkyl, phenyl or benzyl, preferably C1~C 10 The straight-chain alkyl group, phenyl group or benzyl group is preferably a C3-C5 straight-chain alkyl group, phenyl group or benzyl group.

[0060] Furthermore, the X in Chemical Formula 1 is a halogen atom or -OH, and is preferably -Cl, -Br, -I or -OH.

[0061] The electron transfer body of the present invention is obtained by surface-modifying metal oxide nanoparticles with the above-mentioned phosphonium salt. Due to the high reactivity of phosphonium cations, it is easy to form a bond with the metal oxide nanoparticles. It is evenly dispersed in an organic solvent through the repulsive force between substituents and the steric effect. When coated, it can form a uniform ultra-thin film (10 to 100 nm) and is easily applicable as an electron transfer layer of a solar cell.

[0062] In the electron transfer composition, the metal oxide nanoparticles include oxides containing one or more metals selected from tin (Sn), zirconium (Zr), strontium (Sr), zinc (Zn), vanadium (V), molybdenum (Mo), tungsten (W), niobium (Nb), aluminum (Al) and gallium (Ga). As a preferred example of the metal oxide nanoparticles, the metal oxide nanoparticles include one or more metals selected from SnO2, ZnO, TiO2, CeO2, ZrO2, WO3, Zn2SnO4, BaSnO3 and SrTiO3, and more preferably, may include one or more metals selected from SnO2, ZnO, TiO2, CeO2 and ZrO2.

[0063] Furthermore, the particle size of the metal oxide nanoparticles may be 2 to 100 nm, preferably 2 to 50 nm, and more preferably 2 to 20 nm. At this time, when the particle size of the metal oxide nanoparticles is greater than 100 nm, it may be difficult to form a thin and uniform film, and when the particle size is less than 2 nm, it may be difficult to prepare and purchase in practice.

[0064] The electron mediator can be synthesized by the following method.

[0065] The electron carrier of the present invention can be prepared by performing a process comprising: a first step of preparing metal oxide nanoparticles; and a second step of reacting the metal oxide with the compound represented by the above chemical formula 1 to prepare surface-modified metal oxide nanoparticles.

[0066] More specifically, the first step can be prepared by executing a process, which includes: step 1-1, mixing a metal precursor and ultrapure water to prepare a metal precursor solution; step 1-2, adding an alkaline aqueous solution to the metal precursor solution to prepare a reaction solution; step 1-3, performing hydrothermal synthesis on the reaction solution to obtain metal oxide nanoparticles from the hydrothermal synthesis.

[0067] The metal precursor solution of step 1-1 may include a metal precursor and ultrapure water, and the concentration of the metal precursor in the metal precursor solution is 0.2 to 2.0 M, preferably 0.3 to 1.5 M. At this time, when the concentration of the metal precursor in the metal precursor solution is less than 0.2 M, the amount of metal oxide nanoparticles obtained may be too small, and when the concentration of the metal precursor in the metal precursor solution is greater than 2.0 M, the viscosity of the metal precursor aqueous solution increases, and when prepared under the same process conditions, the size of the metal oxide nanoparticles is unevenly formed, and there may be a problem that uniform nanoparticles cannot be obtained.

[0068] At this time, the above-mentioned metal precursor is an organic metal compound including one or more metals selected from tin (Sn), zirconium (Zr), strontium (Sr), zinc (Zn), vanadium (V), molybdenum (Mo), tungsten (W), niobium (Nb), aluminum (Al) and gallium (Ga). As a preferred example, as a metal precursor, it can include halides of the above-mentioned metals, preferably, chlorides of the above-mentioned metals.

[0069] The alkaline aqueous solution in the above step 1-2 may include one or more selected from KOH aqueous solution, NaOH aqueous solution, hydrazine aqueous solution and NH4OH aqueous solution. In addition, the amount of alkaline aqueous solution used is added to the metal precursor solution in such a manner that the pH of the reaction solution becomes 8.0 or more, preferably pH 8.0 to pH 10.0, and more preferably pH 8.0 to 9.0. At this time, when the pH is less than 8, the amount of metal oxide nanoparticles obtained may be too small, and when the pH is less than 8, that is, 6.0 or more and less than 8.0, the metal precursor solution gels, and there may be a problem of being unable to stir evenly. When the pH is too high, there may be a problem of the particle size of the metal oxide particles being too large.

[0070] The hydrothermal synthesis of the above steps 1-3 can be performed by a conventional hydrothermal synthesis method used in this field. The above hydrothermal synthesis is performed at 100-200°C, preferably 110-190°C, and more preferably 120-180°C for 6-48 hours, preferably 10-24 hours, and more preferably 12-18 hours. At this time, when the hydrothermal synthesis temperature is less than 100°C, there may be a problem of low crystallinity of the metal oxide, and when it is greater than 200°C, there may be a problem of increased size of the metal oxide particles. In addition, when the hydrothermal synthesis time is less than 6 hours, there may be a problem of too low yield of metal oxide nanoparticles, and when it is greater than 48 hours, there may be a problem of too large size of the hydrothermal synthesized product, so it is preferred to perform the hydrothermal synthesis within the above time.

[0071] The metal oxide nanoparticles obtained by hydrothermal synthesis can be repeatedly washed 3 to 5 times with ultrapure water and ethanol.

[0072] The particle size of the metal oxide nanoparticles obtained in this way is 2 to 100 nm, preferably, the average particle size is 2 to 50 nm, more preferably, the average particle size is 2 to 20 nm, and even more preferably, it can be 2 to 10 nm.

[0073] Furthermore, the metal oxide nanoparticles are as described above.

[0074] Then, the second step is a process for modifying the surface of the metal oxide nanoparticles obtained in the first step, and a process can be performed, which includes: step 2-1, mixing the metal oxide nanoparticles, C3~C5 alcohols and an aqueous solution containing the compound represented by the above chemical formula 1 to prepare a reaction solution; step 2-2, performing a stirring reaction on the reaction solution; step 2-3, separating the reaction product from the solution subjected to the stirring reaction, and washing the separated reaction product; and step 2-4, obtaining surface-modified metal oxide nanoparticles by drying the washed reaction product.

[0075] In the above reaction solution composition, the above C3-C5 alcohol plays a role in preventing the surface-modified SnO2 particles from agglomerating, and preferably, 2-propanol (2-propanol) can be used. And, regarding its usage, 80 to 200 parts by weight are used in 100 parts by weight of the metal oxide nanoparticles, and preferably, 100 to 180 parts by weight can be used. At this time, when the usage of the C3-C5 alcohol is less than 80 parts by weight, the surface modification reaction may not be carried out well, and when it is greater than 200 parts by weight, it may be difficult to obtain modified nanoparticles.

[0076] Regarding the above-mentioned reaction solution, in 100 parts by weight of the metal oxide nanoparticles, 100 to 220 parts by weight, including 120 to 200 parts by weight, and more preferably, 130 to 180 parts by weight of an aqueous solution containing the compound represented by the above-mentioned chemical formula 1 may be included. At this time, when the amount of the aqueous solution containing the compound represented by the chemical formula 1 used is less than 100 parts by weight, the solvent cannot be fully stirred in the surface modification process, resulting in the possibility of uneven surface modification. When it is greater than 220 parts by weight, there may be a problem of too long stirring reaction time.

[0077] Furthermore, in the aqueous solution including the compound represented by the above Chemical Formula 1, the content of the compound represented by Chemical Formula 1 is 10 to 80% by weight, preferably 30 to 80% by weight, and more preferably 30 to 70% by weight. At this time, when the content of the compound represented by Chemical Formula 1 is less than 10% by weight, the degree of modification of the metal oxide surface is too small or uneven, resulting in the problem that the metal oxide particles cannot be uniformly dispersed in the solvent and precipitate. When it is greater than 80.0% by weight, it is not economical, and there is a problem that the purity of the electron transporter is reduced due to unreacted compounds. Therefore, it is preferably used within the above range.

[0078] The stirring reaction is performed at room temperature for 5 minutes to 2 hours, preferably, for 10 minutes to 1 hour. At this time, when the stirring reaction time is less than 5 minutes, there may be a problem of insufficient stirring, and when it is greater than 2 hours, there is a disadvantage of being uneconomical.

[0079] The separation and / or washing of steps 2-4 can be performed according to conventional methods used in the field. As an example, centrifugal separation can be performed, and after the stirred reaction product is obtained from the reaction solution, it can be washed with ultrapure water or the like.

[0080] The drying in step 2-5 can be performed according to a conventional method used in this field. As an example, the drying can be performed by heating the reaction product obtained by washing in an oven at 50 to 80°C.

[0081] The electron carrier of the present invention may include 85 to 95 weight % of the above-mentioned metal oxide nanoparticles and the remaining surface-modified components in the total weight, preferably, includes 88 to 94 weight % of the above-mentioned metal oxide nanoparticles and the remaining surface-modified components, and more preferably, includes 90.0 to 94.0 weight % of the above-mentioned metal oxide nanoparticles and the remaining surface-modified components.

[0082] The coating agent for an electron transport layer (ETL) of a perovskite solar cell of the present invention utilizes the electron transporter as described above, and includes an organic solvent and the electron transporter dispersed in the organic solvent.

[0083] Furthermore, the organic solvent may have a dielectric constant of 20 or less, preferably, a dielectric constant of 5 to 15. Specific examples of such organic solvents may include one or more selected from isopropanol, butanol, 2,2,2-trifluoroethanol, chlorobenzene and chloroform. Preferably, one or more selected from isopropanol, 2,2,2-trifluoroethanol and chlorobenzene may be used alone or in combination.

[0084] When an organic solvent having a dielectric constant greater than 20 is used, there is a possibility that the organic solvent may cause decomposition of the perovskite as the light absorbing layer during formation of the electron transport layer as a thin film.

[0085] The ETL coating agent of the present invention comprises 0.30-2.00 wt % of the electron carrier and the balance of an organic solvent in the total weight, preferably 0.30-1.50 wt % of the electron carrier and the balance of an organic solvent, and more preferably 0.35-1.00 wt % of the electron carrier and the balance of an organic solvent.

[0086] At this time, when the content of the electron transfer body in the coating agent is less than 0.30 wt %, the content of the electron transfer body is insufficient, and there may be a problem that the light absorption layer is exposed when the ETL film is formed. When it is greater than 2.00 wt %, the thickness of the ETL increases, and there may be a problem that the short-circuit current (J) of the solar cell is increased. sc ) and open voltage (V oc) value is reduced, and thus preferably, an electron carrier is included in the above range.

[0087] The coating agent for forming the ETL of the present invention as described above can be applied by conventional coating methods such as spin coating, blade coating, bar coating, spray coating, gravure coating, and mold coating. As an example, after coating, it can be heat-treated to below 200° C. to form an ultra-thin film with a thickness of 10 to 100 nm or less, preferably, 10 to 70 nm, and more preferably, 10 to 50 nm.

[0088] An inverted structure or PIN structure perovskite solar cell can be prepared as follows using the above-mentioned coating agent of the present invention.

[0089] The inverse structure perovskite solar cell of the present invention can be a solar cell with a structure in which a conductive substrate, a drain electrode, a hole transport layer (HTL), a light absorption layer (or photoactive layer), an electron transfer layer (or electron transport layer, ETL) and a source electrode are stacked in sequence.

[0090] Furthermore, the perovskite solar cell may further include a passivation layer between the light absorption layer and the electron transfer layer. In this case, the passivation layer may include a selected 60 Fullerene, C 70 Fullerene, C 72 Fullerene, C 76 Fullerene and C 84 One or more types of fullerenes.

[0091] Furthermore, the inverse structure perovskite solar cell of the present invention is composed of a group of conductive substrate, drain electrode, hole transport layer, light absorption layer, electron transfer layer and source electrode stacked in sequence, and can also be composed of a single layer or multiple layers of the above group stacked together.

[0092] The above-mentioned conductive substrate can use a common conductive substrate used in this field. As an example, a transparent plastic substrate, a glass substrate, a quartz substrate, a silicon substrate, etc. prepared from raw materials such as polyethylene terephthalate, polyethylene naphthalate, polyether sulfone, aromatic polyester or polyimide can be used.

[0093] The above-mentioned drain electrode can be prepared from one or more raw materials selected from conductive metals, conductive metal alloys, metal oxides and conductive polymers. As a preferred example, it can include indium tin oxide (ITO), fluorine doped tin oxide (FTO), Sb2O3 doped tin oxide (ATO, Sb2O3doped Tin Oxide), gallium doped tin oxide (GTO, Gallium doped Tin Oxide), tin doped zinc oxide (ZTO, tin doped zinc oxide), gallium doped ZTO (ZTO: Ga, gallium doped ZTO), indium gallium zinc oxide (IGZO, Indium gallium zinc oxide), indium doped zinc oxide (IZO, Indium doped zinc oxide) and / or aluminum doped zinc oxide (AZO, Aluminum doped zinc oxide), etc.

[0094] Furthermore, the hole transport layer (HTL) may include inorganic and / or organic hole transport materials. The inorganic hole transport materials may include nickel oxide (NiO x ), CuSC N, CuCrO2 and CuI.

[0095] The organic hole transporting material may include carbazole derivatives, polyarylalkane derivatives, phenylenediamine derivatives, arylamine derivatives, amino-substituted chalcone derivatives, styryl anthracene derivatives, fluorene derivatives, hydrazone derivatives, stilbene derivatives, silazane derivatives, aromatic tertiary amine compounds, styrylamine compounds, aromatic dimethylimine compounds, porphyrin compounds, phthalocyanine compounds, polythiophene derivatives, polypyrrole derivatives, poly(p-phenylene vinylene) derivatives, pentacene, coumarin 6 (3-(2-benzothiazolyl)-7-(diethylamino)coumarin), zinc phthalocyanine (ZnPC), copper phthalocyanine (CuPC), titanium oxide phthalocyanine (TiOPC), and the like. oxidephthalocyanine), spiromethyl-MeOTAD (2,2',7,7'-tetrakis(N,Np-dimethoxyphenylamino)-9,9'-spirobifluorene), copper(II)1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31H-phthalocyanine (F16CuPC, copper(II)1,2,3,4,8,9,10,11,15,16,17,18,22,23,24,25-hexadecafluoro-29H,31H-phthalocyanine), boron subphthalocyanine chloride (SubPc, boron subphthalocyanine chloride) and N3(cis-di(thiocyanato)-bis(2,2'-bipyridyl-4,4'-dicarboxyl ic acid)-ruthenium(II)), poly[3-hexylthi ophene] (P3HT), poly[2-methoxy-5-(3',7'-dimethyloctyloxy)]-1,4-phenylenevinylene (MDMO-PPV ...4-phen ylene vinylene), poly[2-methoxy-5-(2"-ethylhexyloxy)-p-phenylene vinylene] (MEH-PPV), poly(3-octyl thiophene) (P3OT, poly(3-octyl thiophene)), poly(octyl thiophene) (POT, poly(octyl thiophene)), poly(3-decyl thiophene) (P3DT, poly(3-decyl thiophene)), poly(3-dodecyl thiophene) (P3D DT, poly(3-dodecyl thiophene)), poly(p-phenylene vinylene) (PPV, poly(pp henylenevinylene), TFB (poly(9,9'-dioctylfluorene-co-N-(4-butylphenyl)dip henyl amine), polyaniline, Spiro-MeOTAD ([2,22',7,77'-tetrakisN,N-di-pmethoxyphenyl amine)-9,9,9'-spiroborofluoride) ifluorine])), CuSCN, CuI, poly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl]](PCPDTBT, (Po ly[2,1,3-benzothiadiazole-4,7-diyl[4,4-bis(2-ethylhexyl-4H-cyclopenta[2,1-b:3,4-b']dithiophene-2,6-diyl]]), poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl] (Si-PCPDTBT, (poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(2,1,3-benzothiadiazole)-4,7-diyl])), poly(4,8-diethylhexyl) (PBDTTPD, (poly(4,8-diethylhexyloxyl)), poly[2,7-(9-(2-ethylhexyl)-9-hexylfluorene)-alt-5,5-(4',7,-di-2-thienyl-2',1',3'-benzothiadiazole)](PFDTBT,(poly[2,7-(9-(2-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4',7,-di-2-thienyl-2',1',3'-benzothiadiazole)] hienyl-2',1',3'-benzothiadiazole)])), poly[2,7-.9,9-(dioctylfluorene)-alt-5,5-(4',7'-di-2-thienyl-2',1',3'-benzothiadiazole)] (PFO-DBT, (poly[2,7-.9,9-(dioctyl-fluorene)-alt-5,5-(4',7'-di-2-thienyl-2',1',3'-benzothiadiazole)] enyl-2',1',3'-benzothiadiazole)])), poly[(2,7-dioctylsilylfluorene)-2,7-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5,5'-diyl] (PSiFDTBT, (poly[(2,7-dioctylsilafluorene)-2,7-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadiazole)-5,5'-diyl])), poly[[9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thiophenediyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thiophenediyl] (PC DTBT, (Poly[[9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thiophenediyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thiophenediyl])), poly(9,9′-dioctylfluorene-co-bis(N,N′-(4,butylphenyl))bis(N,N′-phenyl-1,4-phenylene)diamine) (PFB, (poly(9, 9′-dioctylfluorene-co-bis(N,N′-(4,butylphenyl))bis(N,N′-phenyl-1,4-phenylene)diamine)), poly(9,9′-dioctylfluorene-cobenzothiadiazole) (F8BT, (poly(9,9′-dioctylfluorene-cobenzothiadiazole)), poly(3,4-ethylenedioxythiophene) (PEDOT, (poly(3,4-ethylenedioxythiophene))), PEDOT:PSS poly(3,4-ethylenedioxythiophene)poly(styrenesulfonate)), polytriarylamine (PTAA, poly(triarylamine)), 2-PACz, Me-2PACz, 4-PACz, MeO-4PACz, Me-4PACz and / or MeO-2PACz. ,

[0096] The hole transport layer may be formed by coating or vacuum deposition. The coating may be formed by gravure coating, bar coating, printing, sputtering, spin coating, dip coating, or die coating.

[0097] Furthermore, in the solar cell composition of the present invention, the light absorbing layer may include a common perovskite raw material suitable for a light absorbing layer of a solar cell, and as a preferred example, may include a perovskite represented by the following Chemical Formula 2.

[0098] Chemical formula 2

[0099] CMX3

[0100] In Formula 2, C is a monovalent cation, which may include amines, ammonium, group I metals, group II metals and / or other cations or cation-like compounds, preferably formamidinium (FA), methylammonium (MA), FAMA, CsFAMA or N(R)4 + (wherein, R may be the same or different groups, and R is a straight-chain alkyl group having 1 to 5 carbon atoms, a branched-chain alkyl group having 3 to 5 carbon atoms, a phenyl group, an alkylphenyl group, an alkoxyphenyl group or an alkyl halide).

[0101] In addition, M in Chemical Formula 2 is a divalent cation, which may include one or two selected from Fe, Co, Ni, Cu, Sn, Pb, Bi, Ge, Ti, Eu, and Zr.

[0102] In addition, X in Chemical Formula 2 is a monovalent anion, which may include one or more halide elements selected from F, Cl, Br and I and / or a Group 16 anion. As a preferred example, X may be I x Br 3-x (0≤x≤3).

[0103] Furthermore, a preferred example of the above chemical formula 2 is FAPbI x Br 3-x (0≤x≤3), MAPbIx Br 3-x (0≤x≤3), CsMAFAPbI x Br 3-x (0≤x≤3), CH3NH3PbX3(X=Cl, Br, I, BrI2 or Br2I), CH3NH3SnX3(X=Cl, Br or I), CH(=NH)NH3PbX3(X=Cl, Br, I, BrI2 or Br2I), CH(=NH)NH3SnX3(X=Cl, Br or I), etc.

[0104] Furthermore, in the solar cell of the present invention, the light absorption layer may be a single layer composed of the same perovskite or a multilayer structure composed of multiple layers composed of other perovskite, and may include the above-mentioned perovskite and other heterogeneous perovskites having columnar, plate-like, needle-like, linear, rod-like or other pillar shapes inside the light absorption layer composed of one perovskite.

[0105] In the solar cell composition of the present invention, regarding the electron transfer layer, the coating agent of the present invention as described above (a dispersion of surface-modified metal oxide nanoparticles dispersed in an organic solvent, an electron transfer body) can be coated with a coating liquid, and then low-temperature heat treatment is performed at a temperature below 200°C, preferably below 30 to 100°C, to form a coating layer in the form of a thin film, so that the electron transfer layer is formed on the upper part of the light absorption layer.

[0106] At this time, the coating may be performed by spin coating, blade coating, bar coating, spray coating, gravure coating or die coating.

[0107] Furthermore, the thickness of the electron transport layer is 10 to 100 nm, preferably 10 to 70 nm, and more preferably 10 to 50 nm. When the thickness of the electron transport layer is greater than 200 nm, the short circuit current (J sc ) and open voltage (V oc ) is reduced, and thus it is preferably formed with a thickness within the above range.

[0108] The coating layer formed in this manner, that is, the surface of the electron transport layer can be formed to have a very low roughness, with a root mean square (RMS) roughness of 50 nm or less, preferably 5.00 to 30.00 nm, and more preferably 10.00 to 25.00 nm.

[0109] Furthermore, in the solar cell composition of the present invention, the above-mentioned source electrode can be formed by coating or depositing one or more substances selected from Pt, Au, Ni, Cu, Ag, In, Ru, Pd, Rh, Ir, Os, C and conductive polymers.

[0110] The present invention can be applied to heterojunction (tandem) perovskite solar cells. As an example, a heterojunction perovskite solar cell can be a solar cell with a structure in which a conductive substrate, a drain electrode, a first light absorbing layer (or a first photoactive layer), a composite layer, a hole transport layer (HTL), a second light absorbing layer (or a second photoactive layer), an electron transport layer (or an electron transport layer, ETL) and a source electrode are stacked in sequence.

[0111] The first light absorbing layer may be a silicon solar cell or a light absorbing layer including the perovskite as described above.

[0112] When the first light absorbing layer is a silicon solar cell, it can be a p-type silicon layer or an n-type silicon layer, and thus, the doping layer can be n-type or p-type. When perovskite is included, a hole transport layer and an electron transfer layer can be included between the drain and the light absorbing layer and between the light absorbing layer and the composite layer, respectively.

[0113] The above-mentioned conductive substrate, drain electrode, hole transport layer, second light absorption layer, electron transfer layer, and source electrode are the same as those described in the above-mentioned inverse structure perovskite solar cell.

[0114] Furthermore, the perovskite solar cell may further include a passivation layer between the second light absorbing layer and the electron transport layer. In this case, the passivation layer may include a selected 60 Fullerene, C 70 Fullerene, C 72 Fullerene, C 76 Fullerene and C 84 One or more types of fullerenes.

[0115] Hereinafter, the present invention will be described in more detail by way of examples. However, the following examples do not limit the scope of the present invention and should be construed as helping to understand the present invention.

[0116] Example

[0117] Example 1-1: Preparation of coating solution for forming electron transport layer (ETL)

[0118] (1) Preparation of SnO2 nanoparticles

[0119] SnCl45H2O was added to a beaker filled with ultrapure water and stirred to prepare a metal precursor solution with a SnCl4 concentration of 0.5 M. Then, 85 mL of NH4OH as an alkaline aqueous solution was added to 215 mL of the metal precursor solution to prepare a reaction solution with a pH of about 8.0 to 8.5.

[0120] The reactive solution was placed in a pressure vessel (autoclave or hydrothermal reactor), and hydrothermal synthesis was performed at 120° C. for 12 hours.

[0121] Then, the product obtained by hydrothermal synthesis was washed 3 to 5 times with ultrapure water and ethanol to prepare SnO2 nanoparticles.

[0122] The average particle size of the prepared SnO2 nanoparticles is 3 to 5 nm.

[0123] In addition, the TEM image of the prepared SnO2 nanoparticles is shown in Figure 1 The XRD measurement results are shown in Figure 2 middle.

[0124] (2) Preparation of electron carriers (surface-modified SnO2 nanoparticles)

[0125] 5 g of the SnO2 nanoparticles prepared above were placed in a round-bottom flask filled with 7.5 mL of 2-propanol and stirred, and then 7.5 mL of an aqueous solution containing 40 wt % of the compound (TBPH) represented by the following chemical formula 1-1 was added, and then a reaction solution was prepared using an ultrasonic pulverizer.

[0126] Chemical formula 1-1

[0127]

[0128] In Chemical Formula 1-1, R 1 To R 4 They are n-butyl, respectively, and the above X is -OH.

[0129] Then, the nanoparticles were separated from the reaction solution using a centrifugal separator and then dried in an oven at 60° C. to prepare surface-modified SnO 2 nanoparticles (electron mediator) as an electron mediator.

[0130] Experimental Example 1: FT-IR and TGA analysis of electron transporters

[0131] The SnO2 nanoparticles prepared in Example 1-1 before and after surface modification were subjected to Fourier transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA). The results are shown in Figure 3 and Figure 4 middle.

[0132] (1) Figure 3 are the FT-IR measurement results. The black curve is the measurement result of SnO2 nanoparticles before surface modification, and the red curve is the measurement result of SnO2 nanoparticles after surface modification.

[0133] View Figure 3 After surface modification, it can be confirmed that there is a peak at about 2870-2980cm -1 The ν(CH2) peak is about 1460cm -1 δ as (CH) peak k, about 1380cm -1 The CH2 peak of SnO2 nanoparticles confirms the presence of tetrabutylphosphonium hydroxide (TBPH) as a modifying component on the surface of SnO2 nanoparticles.

[0134] (2) Furthermore, Figure 4 The results of TGA analysis show that when SnO2 nanoparticles before and after surface modification are heated to 700°C, the unmodified SnO2 nanoparticles (bare SnO2) (black curve) lose about 8% of their mass relative to the initial input amount due to the removal of surface adsorbed moisture and -OH, etc. On the contrary, the surface modified SnO2 nanoparticles (TBPH modifiedSnO2) show a sharp decrease in mass at about 200-350°C, and lose about 16% of their mass at 700°C.

[0135] Thus, it can be confirmed that the surface-modified SnO2 nanoparticles contain about 8% of organic matter compared to the unmodified SnO2 nanoparticles, and it can be confirmed that the electron carrier prepared thereby contains 92 wt% of SnO2 nanoparticles and 8 wt% of the surface-modified component.

[0136] Comparative Example 1-1

[0137] When the surface modification step is not required, the SnO 2 nanoparticles prepared in (1) of Example 1-1 are prepared as an electron mediator.

[0138] Comparative Example 1-2

[0139] The SnO2 nanoparticles prepared in (1) of Example 1-1 were prepared.

[0140] Then, 5 g of the SnO2 nanoparticles were placed in a round-bottom flask filled with 3 mL of ultrapure water and stirred, and then 7.5 mL of a 40 wt% aqueous solution of tetrabutylammonium hydroxide (TBAH) was added, and then a reaction solution was prepared using an ultrasonic pulverizer. Then, the nanoparticles were separated from the reaction solution using a centrifuge, and then dried in an oven at 60° C. to prepare SnO2 nanoparticles (electron transporters) surface-modified by TBAH.

[0141] Comparative Examples 1-3

[0142] The SnO2 nanoparticles prepared in (1) of Example 1-1 were prepared.

[0143] Then, 5 g of the SnO2 nanoparticles were placed in a round-bottom flask filled with 3 mL of ultrapure water and stirred, and then 30 mL of a 10 wt% aqueous solution of tetramethylammonium hydroxide (TMAH) was added, and then a reaction solution was prepared using an ultrasonic pulverizer. Then, the nanoparticles were separated from the reaction solution using a centrifuge, and then dried in an oven at 60°C to prepare SnO2 nanoparticles (electron transporters) surface-modified by TMAH.

[0144] Example 2-1: Preparation of a dispersion solution of an electron transporter (coating solution for forming an ETL)

[0145] The electron transporter 7.0Mg prepared in Example 1-1 was added to 1.0 ml of 2,2,2-trifluoroethanol (2,2,2-Trifluoroethanol, dielectric constant = about 8.5) having low hydrophilicity, and then a dispersion type electron transport layer forming coating liquid was prepared using an ultrasonic pulverizer.

[0146] Experimental Example 2: Measurement of dispersibility (dispersion stability) of coating liquid

[0147] The dispersibility of the ETL-forming coating solutions prepared in Example 2-1 and Comparative Examples 2-1 to 2-3 was measured using a dynamic light scattering particle size analyzer, and the results are shown in Table 2 below. The Z-average value was evaluated to be below 20.0 nm, preferably below 17.0 nm, to have excellent dispersion stability, and the evaluation value in Table 1 is the average value of three repeated measurements of the experiment. At this time, the worse the dispersibility, the more the particle size distribution forms multiple peaks instead of a single peak.

[0148] In addition, the measurement results of Example 2-1 (TBPH), Comparative Example 2-2 (TBAH) and Comparative Example 2-3 (TMAH) are shown in the graph. Figure 5 In the embodiment 2-1, the comparative example 2-2 and the comparative example 2-3 all form a single peak under the same conditions.

[0149] Table 1

[0150]

[0151] According to the experimental results in Table 1, the coating liquid prepared by the SnO2 nanoparticles without surface modification has poor dispersibility, showing an unmeasurable result. In addition, the coating liquid prepared by using the nanoparticles of Comparative Examples 1-2 and 1-3 as electron carriers, that is, Comparative Examples 2-2 and 2-3 have outstanding dispersibility compared to Comparative Example 2-1, but show a tendency of relatively lower dispersibility compared to Example 2-1.

[0152] Example 2-2 to Example 2-3 and Comparative Examples 2-4 to 2-5

[0153] The coating liquid for forming an electron transport layer was prepared in the same manner as in the above-mentioned Example 2-1. As shown in the following Table 3, the type of organic solvent used to prepare the coating liquid was changed to prepare the coating liquid for forming an ETL, and Examples 2-2 to 2-3 and Comparative Examples 2-4 to 2-5 were implemented (see Table 2).

[0154] Table 2

[0155]

[0156] Experimental Example 2: Preparation of Ultra-Thin Film and Measurement of Surface Roughness and Light Transmittance of Coating Layer

[0157] The ETL forming coating liquid prepared in the above Examples 2-1 to 2-3 and Comparative Examples 2-4 to 2-5 was spin-coated on the perovskite thin film including the glass substrate and the upper part of the glass substrate, respectively, and then heat-treated at 30° C. to prepare an ultra-thin film with a thickness of 10 to 15 nm.

[0158] Furthermore, after measuring the surface roughness of the ultra-thin film formed on the upper part of the perovskite film including the glass substrate by a non-contact method, the surface roughness of any three points was calculated using the root mean square (rms) of the roughness. After measuring the surface roughness of the three points, the average value of the surface roughness of the three points measured is shown in the following Table 4.

[0159] In addition, regarding the above-mentioned ultra-thin film formed on the glass substrate, near-infrared light is injected into the substrate formed with the ultra-thin film using a UV spectroscopy method to measure the absorbance and light transmittance (tranmittance, %) of the sample. The results are shown in the following Table 3. At this time, the light transmittance is the light transmittance at a wavelength of 500 to 550 nm.

[0160] Table 3

[0161] distinguish RMS (root mean square) roughness Light transmittance (%) Example 2-1 12.52±1.95nm 91.0% Example 2-2 15.16±4.77nm 91.0% Example 2-3 22.73±1.66nm 90.9% Comparative Examples 2-4 13.35±1.09nm 90.9% Comparative Examples 2-5 Unable to determine 90.9%

[0162] By looking at the RMS roughness and light transmittance in Table 3, it can be confirmed that the RMS roughness of Examples 2-1 and 2-2 is 10.0 to 20.0 nm, which is very low in surface roughness, and has excellent optical properties with a light transmittance of more than 90%. Comparative Example 2-4 shows results with surface roughness and optical properties similar to those of Examples 2-1 and 2-2. In contrast, in Comparative Example 2-5, the optical properties are similar, but when a thin film is formed on the top of the perovskite, the perovskite layer is completely melted, and there is a problem that the roughness cannot be measured.

[0163] Preparation Example 1: Preparation of inverse structure perovskite solar cells using surface modified SnO2 nanoparticles

[0164] As a drain electrode, an organic substrate (thickness: 1.1 mm, 15.0 Ω / sq) coated with indium tin oxide (ITO) with a thickness of about 110 nm was cleaned with acetone and isopropyl alchol (IPA) in sequence by an ultrasonic cleaner for 1 hour each.

[0165] Then, a hole transport layer (NiO) with a thickness of 20 nm was formed on the above-mentioned ITO substrate by sputtering deposition method. x ).

[0166] Then, a yellow light absorbing layer solution dissolved in dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) was formed on the hole transport layer by spin coating, and then heat treated at 100°C for 20 minutes to form NiO x The hole transport layer and the light absorption layer having a perovskite crystal structure with a thickness of 450 to 550 nm (CsMAFAPbI x Br 3-x , 0≤x≤3).

[0167] Then, a LiF film with a thickness of less than 1 nm and a passivation layer (C) with a thickness of 13 nm were formed on the upper portion of the light absorbing layer by thermal evaporation. 60 Fullerene).

[0168] Then, the ETL forming coating liquid prepared in Example 2-1 was spin-coated on the passivation layer at 4000 rpm for 30 seconds, and then heat-treated at 30° C. to form an electron transport layer with a thickness of 15 nm. Then, indium doped zinc oxide (IZO) was formed as a transparent electrode layer with a thickness of 100 nm on the hole transport layer by sputtering equipment.

[0169] Then, on the upper part of the electron transport layer, at 1×10 -7 Silver (Ag) was deposited at a thickness of 200 nm under a pressure of torr to form a source electrode to prepare an inverse structure perovskite solar cell.

[0170] Preparation Examples 2 to 3 and Comparative Preparation Examples 1 to 3

[0171] An inverse-structured perovskite solar cell was prepared using the same method as in Preparation Example 1, using the ETL-forming coating liquids of Examples 2-2 to 2-7 and Comparative Examples 2-2 to 2-6 instead of the ETL-forming coating liquid of Example 2-1 to prepare solar cells forming an electron transfer layer, respectively, and implementing Preparation Examples 2 to 3 and Comparative Preparation Examples 1 to 3, respectively.

[0172] Control group: Solar cell with electron transport layer formed by ALD deposition

[0173] As a control group, a drain electrode, a hole transport layer, a perovskite light absorption layer, and a passivation layer were formed by the same method as in the above-mentioned preparation example 1, and then a SnO layer with a thickness of 6 nm was formed on the upper part of the above-mentioned passivation layer by atomic layer deposition. x Deposition layer (electron transport layer).

[0174] Then, on the upper part of the electron transport layer, at 1×10 -8 Silver (Ag) was deposited at a thickness of 150nm under a pressure of torr to form a source electrode to prepare an inverse structure perovskite solar cell.

[0175] Experimental Example 2: Performance Measurement of Semi-transparent Solar Cells

[0176] The current-voltage characteristics and efficiency of the semi-transparent solar cell prepared in the above-mentioned Preparation Example 1 were measured, and the results are shown in the following Table 4. In addition, the short-circuit current density and photoelectric conversion efficiency (PCE) measurement results of Preparation Example 1 and the control group are shown in Figure 6 middle.

[0177] Table 4

[0178]

[0179] From the results of the solar cell performance measurement in Table 4, Preparation Example 1 exhibited solar cell performance (current-voltage characteristics, fill factor, photoelectric conversion efficiency) similar to that of a solar cell composed of an ETL formed by ALD deposition. In contrast, in Comparative Preparation Example 1, in which the ETL was formed by introducing SnO2 nanoparticles surface-modified with TBAH (Comparative Example 2-2) into a coating liquid as a raw material of an electron transfer agent, there was a problem of a decrease in fill factor compared to Preparation Example 1. This is because TBAH, a surface modification component of an electron transfer agent, and the fullerene raw material (C 60 ) reacts, damaging the passivation layer and causing the performance of the solar cell to deteriorate.

[0180] In contrast, the solar cell of Comparative Preparation Example 2 showed no such passivation layer damage, but showed slightly lower performance than Preparation Example 1. This can be inferred to be the result of the dispersion of the dispersion solution being lower than that used in Preparation Example 1, resulting in reduced film density and uniformity.

[0181] Furthermore, in Comparative Preparation Example 2 in which ETL was formed by a coating liquid containing isopropyl alcohol as an organic solvent in the ETL-forming coating liquid (Example 2-2) and Comparative Preparation Example 3 in which ETL was formed by a coating liquid containing chlorobenzene as an organic solvent (Example 2-3), the performance of the solar cell was reduced. This was caused by a problem in which the uniformity of the film was reduced due to a slightly low dispersion of the electron transfer body in the ETL-forming coating liquid.

[0182] Furthermore, in Comparative Preparation Example 4 in which the ETL was formed from a coating solution using ethanol (EtOH) as an organic solvent, it was confirmed that ethanol as an organic solvent damaged the perovskite photoactive layer, resulting in a problem of reduced performance of the solar cell element.

[0183] Preparation Example 4: Preparation of tandem perovskite solar cells using surface-modified SnO2 nanoparticles

[0184] As the lower solar cell, a cell having a PERC structure is used.

[0185] The above PERC structure unit is formed by a POCl process on a p-type impurity-doped silicon substrate formed with a lower passivation layer and a lower electrode made by Qcells Korea. ++ Emitter layer.

[0186] Then, in n ++ On the emitter layer, an indium tin oxide (ITO) layer is formed as a composite layer with a thickness of 50 nm by a sputtering device.

[0187] Then, a hole transport layer (NiO) with a thickness of 20 nm was formed on the above-mentioned ITO substrate by sputtering deposition method. x ).

[0188] Then, a yellow light absorbing layer solution dissolved in dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) was formed on the hole transport layer by spin coating, and then heat treated at 100°C for 20 minutes to form NiO x The hole transport layer and the light absorption layer having a perovskite crystal structure with a thickness of 450 to 550 nm (CsMAFAPbI x Br 3-x (0≤x≤3)).

[0189] Then, a LiF thin film with a thickness of less than 1 nm and a passivation layer (C) with a thickness of 13 nm were formed on the upper portion of the light absorbing layer by thermal evaporation. 60 Fullerene).

[0190] Then, the ETL forming coating liquid prepared in Example 2-1 was spin-coated on the passivation layer at 4000 rpm for 30 seconds, and then heat-treated at 30° C. to form an electron transport layer with a thickness of 15 nm. Then, indium doped zinc oxide (IZO) or tin doped indium oxide (ITO) was formed as a transparent electrode layer with a thickness of 100 nm on the hole transport layer by sputtering equipment.

[0191] Then, on the upper part of the electron transport layer, at 1×10 -7 Silver (Ag) was deposited at a thickness of 200 nm under a pressure of torr to form a source electrode to prepare a tandem perovskite solar cell.

[0192] (2) Preparation of control group (ALD deposition)

[0193] As a control group, a tandem perovskite solar cell was prepared by the same method as in the above-mentioned preparation example 4. ++ After forming the same hole transport layer, perovskite light absorption layer and passivation layer as those in Preparation Example 4 on the emitter layer, a SnO layer with a thickness of 6 nm was formed on the passivation layer by atomic layer deposition. x Deposition layer (electron transport layer).

[0194] Then, on the upper part of the electron transport layer, at 1×10 -8 Silver (Ag) was deposited at a thickness of 150nm under a pressure of torr to form a source electrode to prepare a tandem perovskite solar cell.

[0195] Comparative Preparation Examples 6 and 7

[0196] A tandem perovskite solar cell was prepared using the same method as in Preparation Example 4, using the ETL forming coating liquids of Comparative Examples 2-2 and 2-3 instead of the ETL forming coating liquid of Example 2-1, respectively, to prepare tandem solar cells forming an electron transfer layer, and comparative preparation examples 6 and 7 were respectively implemented (see Table 5 below).

[0197] Experimental Example 3: Performance measurement of silicon-perovskite tandem solar cells

[0198] The current-voltage characteristics and efficiency of the silicon-perovskite tandem solar cells prepared in the above-mentioned Preparation Example 4, the control group, and the comparative Preparation Examples 6-7 were measured, and the results are shown in the following Table 5. In addition, the short-circuit current density and photoelectric conversion efficiency (PC E) measurement results of Preparation Example 4 and the control group are shown in Figure 7 middle.

[0199] Table 5

[0200]

[0201]

[0202] See Table 5 and Figure 7 The performance test results of the tandem solar cell elements confirm that the tandem solar cell element of Preparation Example 1 has excellent photoelectric conversion efficiency.

Claims

1. An electron transporter for an electron transport layer of a perovskite solar cell, comprising metal oxide nanoparticles surface-modified with a phosphite represented by the following chemical formula 1, characterized in that: Chemical formula 1 In Chemical Formula 1, R 1 To R 4 C1~C 10 Straight chain alkyl, C3~C 10 The above X is a halogen atom or -OH.

2. The electron transporter for the electron transport layer of the perovskite solar cell according to claim 1, characterized in that The above-mentioned metal oxide nanoparticles include oxides containing one or more metals selected from tin (Sn), zirconium (Zr), strontium (Sr), zinc (Zn), vanadium (V), molybdenum (Mo), tungsten (W), niobium (Nb), aluminum (Al) and gallium (Ga).

3. The electron transporter for the electron transport layer of the perovskite solar cell according to claim 1 or 2, characterized in that The total weight of the electron mediator includes 85.0 to 95.0 weight % of the metal oxide nanoparticles and the remaining amount of the surface modification component.

4. The electron transporter for the electron transport layer of the perovskite solar cell according to claim 1, characterized in that The particle size of the metal oxide nanoparticles is 1 to 100 nm.

5. A coating agent for an electron transport layer of a perovskite solar cell, characterized in that: include: Organic solvents; as well as The electron carrier selected from any one of claims 1 to 4 dispersed in the organic solvent, The dielectric constant of the organic solvent is 20 or less.

6. The coating agent for an electron transport layer of a perovskite solar cell according to claim 5, characterized in that: The composition comprises 0.30 to 2.00 wt % of an electron mediator and the remainder of an organic solvent.

7. The coating agent for an electron transport layer of a perovskite solar cell according to claim 5, characterized in that: The organic solvent includes at least one selected from isopropanol, butanol, 2,2,2-trifluoroethanol, chlorobenzene and chloroform.

8. An electron transport layer of a perovskite solar cell, characterized in that: It comprises a coating layer formed of the coating agent according to claim 5.

9. The electron transport layer of the perovskite solar cell according to claim 8, characterized in that: The thickness of the electron transport layer is 10 to 200 nm. When the thickness of the electron transport layer is 10 to 15 nm, the transmittance of light with a wavelength of 500 to 550 nm is 88.0% or more.

10. A perovskite solar cell, characterized in that: The electron transport layer according to claim 8 is directly formed on the upper surface of the perovskite light absorbing layer, or A passivation layer is formed between the perovskite light absorbing layer and the electron transporting layer according to claim 8 .

11. The perovskite solar cell according to claim 10, characterized in that: The passivation layer comprises a 60 Fullerene, C 70 Fullerene, C 72 Fullerene, C 76 Fullerene and C 84 One or more types of fullerenes.